Morphometric evaluation of bone regeneration in segmental mandibular bone defects filled with bovine bone xenografts in a split-mouth rabbit model - Mariana Quirino Silveira Soares; Jeroen Van Dessel; Reinhilde Jacobs; Renato Yassutaka Faria Yaedú; Eduardo Sant'Ana; Danilo da Silva Corrêa; Maria Fernanda Conceição Madeira; Marco Antônio Húngaro Duarte; Izabel Regina Fischer Rubira-Bullen (SpringerOpen, 2019)
Abstract Background Bovine bone grafts have been widely used in dentistry for guided tissue regeneration and can support new bone formation in direct contact with the graft. The aim of this study was to compare the morphometric and bone density changes after using two different bovine bone graft blocks in segmental osseous defects in the mandible of rabbits following different postoperative periods. Material and methods Critical size segmental defects were surgically created bilaterally in the jaw of 18 rabbits. The defects were filled with either deproteinized bovine bone mineral with 10% collagen (DBBM-C; BioOss Collagen®), lyophilized bovine medullary bone (LBMB; Orthogen®), or left untreated according to a split-mouth design. Animals were sacrificed after 3 or 6 months of healing. The hemimandibles were scanned ex vivo using a high-resolution (19 μm) microcomputed tomography. Morphometric and bone density parameters were calculated in the region of the defect using CT-Analyser (Bruker). Initial graft blocks were used as baseline. Results DBBM-C presented a denser microarchitecture, in comparison to LBMB at baseline. DBBM-C and LBMB grafted regions showed a similar progressive remodeling, with a significant decrease in structure complexity and maintenance of bone volume fraction during the postoperative follow-up periods. Both graft materials showed an enhanced bone replacement and more complex structure compared to untreated defects. The apparent fusion between the graft and host bone was observed only in the defects filled with LBMB. Conclusion LBMB grafts showed a similar behavior as DBBM-C regarding structural remodeling. In LBMB samples, apparent integration between the host bone and the graft was present.